Digital Humanities: Nurturing Nationalism Through Social Media - Willfridus Demetrius Siga; Kristining Seva; Chandra Wijaya; Asnita Sirait (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2022)
The transformation of information and communication technology is believed to not only change the context and pattern of social networks but also the perspective in addressing a social problem. The facilitation of the internet medium and cellular technology, for example, has changed the paradigm of nationalism, especially through audiovisual content. Through the mixed method as a research method, namely the combination of quantitative methods (a survey technique for the younger generation with an age range of 18-22 years) and qualitative methods (through a digital ethnographic approach obtained from the “drone emprit academy”), this study shows that the use of social media by the younger generation shows positive trends in maintaining the spirit of nationalism such as uploading topics with the theme of nationalism, Pancasila, and unity. It means that the more content with nationalism nuances that is shared through social media, the greater the awareness and encouragement to maintain the spirit of nationalism.